2006
DOI: 10.1021/om060030w
|View full text |Cite
|
Sign up to set email alerts
|

New Rhodium(I) Carbene Complexes from Carbene Transfer Reactions

Abstract: The Rh(I) complexes RhCl(diene)(NHC) have been synthesized from Ag(I) carbene precursors, where NHC is one of the N-heterocyclic carbenes 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene (IPr), 1,3bis(2,4,6-trimethylphenyl)imidazol-2-ylidene (IMes), 3-methyl-1-phenacylimidazol-2-ylidene (MAI), and 3-methyl-1-picolylimidazol-2-ylidene (MPI), and diene is either NBD or COD. The complexes are characterized by elemental analysis, 1 H NMR and IR spectroscopies, mass spectrometry, and, in the case of RhCl(NBD)(IMes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 41 publications
(47 reference statements)
4
48
0
Order By: Relevance
“…For 3, as well as the high-field doublet resonance for the equivalent hydrides, the 1 H NMR spectrum (in C 6 D 6 ) shows a δ = 6.43 ppm singlet for the NCH proton, a septet signal at δ = 2.92 ppm for the IPr-methine protons, and doublets at δ = 1.34 and 1.02 ppm for two types of Me-groups; the signal integrations and J values support the formulation, as well the 13 C{ 1 H} data, which include a doublet for the carbene carbon at δ = 182.7 ppm (J RhC = 58 Hz), the normal range for carbene-Rh complexes. [13,24] The hydride resonances are also in the range reported for the hydride ligands of Rh(H)Cl(IMesЈ)(IMes), where IMesЈ is the cyclometallated carbene formed from a methyl group via intramolecular C-H activation, [15,18] and of Rh(H) 2 Cl-(IMes) 2 (see below).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…For 3, as well as the high-field doublet resonance for the equivalent hydrides, the 1 H NMR spectrum (in C 6 D 6 ) shows a δ = 6.43 ppm singlet for the NCH proton, a septet signal at δ = 2.92 ppm for the IPr-methine protons, and doublets at δ = 1.34 and 1.02 ppm for two types of Me-groups; the signal integrations and J values support the formulation, as well the 13 C{ 1 H} data, which include a doublet for the carbene carbon at δ = 182.7 ppm (J RhC = 58 Hz), the normal range for carbene-Rh complexes. [13,24] The hydride resonances are also in the range reported for the hydride ligands of Rh(H)Cl(IMesЈ)(IMes), where IMesЈ is the cyclometallated carbene formed from a methyl group via intramolecular C-H activation, [15,18] and of Rh(H) 2 Cl-(IMes) 2 (see below).…”
Section: Resultsmentioning
confidence: 81%
“…[14] We later reported that (carbene-phosphanyl)-Rh I species undergo "standard" oxidative addition of O 2 to give Rh III -peroxide species, [15] while Crudden and co-workers have recently suggested that such species are best considered as Rh I with coordinated singlet oxygen. [16] Our studies [13][14][15] have thus far mainly utilized the simple, unfunctionalized NHCs, N,N-bis (2,6-diisopropylphenyl)imidazol-2-ylidene (IPr) and N,N-bis (2,4,6-trimethylphenyl)imidazol-2-ylidene (IMes) (see Scheme 1), in syntheses of the RhCl(diene)(NHC) and [RhCl(COE)(NHC)] 2 complexes, and reactivities of these complexes with O 2 (diene = NBD or COD, and COE = cyclooctene). Because of our interests in catalytic hydrogenation/hydroformylation, we then studied reactions of the [RhCl(COE)(NHC)] 2 complexes with H 2 and with CO, with an ultimate goal of comparing catalytic activity of such sys-afford the respective dicarbonyl complexes RhCl(CO) 2 (NHC) [NHC = IPr (6), IMes (7)], while CO reactions with the biscarbene dihydrides give, respectively, the mono-carbonyl complex RhCl(CO)(IPr) 2 (8) and the known IMes analogue.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…An important additional route for the generation of NHC-substituted rhodium(I) complexes is the carbene transfer reaction starting from NHC-substituted silver(I) complexes, which was first mentioned by Lin. [29,30] …”
Section: Introductionmentioning
confidence: 99%